Development of multi-entry decisional integration framework (MEDIF) for Malaysian construction firms in international operations / Norizzati Ibrahim - Ibrahim, Norizzati (2022)
The construction industry is critical to the country's economic growth through internationalization. However, the Malaysian construction firms' lack of participation in construction projects abroad is among the problems faced by the industry at present. In addition, no entry decisions using scales in the form of matrices have been developed from prior studies to assist Malaysian construction firms to enter the international market. Hence, a strategic framework in the form of a matrix based on a scale from poor to excellent decision-making is perceivably crucial in providing a clear guide to the Malaysian construction firms in adopting effective international market entry decisions. The current study develops a multi-entry decision integration (MEDIF) framework that is geared towards internationalisation for Malaysian construction firms. Moreover, MEDIF was introduced in parallel with the passage of time due to continuous improvement to achieve excellent decision-making to go abroad. This study utilized a mixed-methods research design, consisting of quantitative and qualitative approaches in realizing this framework. The respondents involved in this study are construction firms that undertook or have completed the projects in the international markets and were registered under the Construction Industry Development Board Malaysia for Class A and Grade 7. The perceptions of the MEDI among respondents with various positions from 74 international construction companies were obtained through a questionnaire survey. Meanwhile, the respondents' and firms' demographics were analyzed using SPSS, and fit items were obtained using the Rasch Model. Next, Structural Equation Modeling (SEM) through Smart PLS analysis was used to obtain the relationship between the key determinants with EL, ET, and EM to be included in the MEDIF. Then, seven (7) experienced construction industry experts were interviewed to obtain their opinions. Therefore, the published MEDIF has been able to identify six key determinants of the sustainability of Malaysian construction firms in the international market. Next, these determinants are measured based on appropriate entry decision level scales, ranging from poor to excellent decision-making, which from 1 to 6 due to the beta coefficient value from the Smart PLS analysis.